Morphological, genotypic, and physiological characterization of Acanthamoeba isolates from keratitis patients and the domestic environment in Vitoria, Espírito Santo, Brazil - Duarte, Juliana L.; Furst, Cinthia; Klisiowicz, Débora R.; Klassen, Giseli; Costa, Adriana O. (Experimental parasitology, 2013)
•Acanthamoeba samples from Vitória, Brazil genotyped as T4 and T11 tolerated 37°C.•One keratitis isolate cultivated in NNA with E. coli survived at 42°C.•All isolates in NNA with E. coli, except one from environment, tolerated 1.0M.•Isolates under axenic condition did not grow at 0.5M and 1.0M.•Osmo-tolerance depended of the culture system. Amoebae of the genus Acanthamoeba are free-living protozoa that can cause granulomatous encephalitis and keratitis in humans. In this study, four clinical and three household dust isolates obtained in Vitória, Espírito Santo, Brazil were characterized by their morphological, genotypic, and physiological properties. All isolates belonged to group II according to Pussard and Pons’ cyst morphology. Analysis of their 18S rDNA sequence identified one isolate from household dust as genotype T11 and the others six samples as genotype T4. Five T4 isolates presented a highly variable region (DF3) in 18S rDNA identical to those previously described. Physiological assays carried out with trophozoites in co-culture with bacteria or in axenic conditions showed all samples tolerated temperatures up to 37°C, regardless of culture method. One keratitis isolate grew at 42°C in co-culture with bacteria. Most isolates in co-culture survived at 1.0M, except a T11 isolate, which tolerated up to 0.5M. The isolates did not grow at 42°C and did not tolerate 0.5M and 1.0M under axenic condition. This is the first report of 18S rRNA gene genotyping applied to Acanthamoeba isolated from keratitis patients in Brazil. The results also indicated that osmo-tolerance is dependent on the culture system.